Body growth in Hawaiian monk seals. Issue 1 (25th April 2013) - Baker, Jason D.; Johanos, Thea C.; Wurth, Tracy A.; Littnan, Charles L.
Abstract Body length and axillary girth measurements of more than 600 free‐ranging Hawaiian monk seals from 1 to 20 yr old were analyzed. Comparison of fitted von Bertalanffy growth models confirmed there is no evidence of sexual dimorphism in this species. Substantial differences in growth patterns were detected among seven subpopulations representing the species entire geographic range. The age at which seals would be expected to attain a reference length of 180 cm ranged from just over 3 yr up to almost 7 yr at the various sites. Subpopulations exhibiting slower growth have previously been found to also exhibit lower age‐specific reproductive rates. Differences in growth of seals among sites likely indicate varying environmental conditions determining growth during the time periods represented in the sampled data.